THE RECONSTRUCTION OF ISLAMIC EDUCATION IN BUILDING THE CIVILISATION OF THE UMMAH THROUGH THE INTEGRATION OF NORMATIVE-DOCTRINAL AND EMPIRICAL APPROACHES - Agung Nugroho; Husnul Yaqin; Hamdan; Hidayat Ma'ruf (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to analyse Islamic educational strategies for building a civilised society through a normative-doctrinal approach based on the Qur’an and Hadith, as well as an empirical examination of the dynamics of the digital age. The issues addressed include the moral crisis, disinformation, and the secularisation of knowledge, which highlight the weak integration of knowledge, faith, and ethics within the education system. This study employs a qualitative approach using library research, with data sources comprising the Qur’an, Hadith, and relevant scholarly literature. Data collection was conducted through documentary analysis, whilst data analysis utilised content analysis with a dialectical approach to examine the relationship between normative ideals and empirical reality.The research findings indicate that an effective Islamic educational strategy must be built integrally through three main pillars: strengthening Tawhid as a foundation of values; developing critical reasoning based on tabayyun and ‘aql as epistemological instruments; and strengthening digital ethics as a practical manifestation in social life. The integration of these three aspects not only addresses the challenges of the digital age but also reinforces the role of Islamic education as a civilisational instrument in shaping individuals who are religious, critical, and of good moral character.